The effect of temperature on low temperature vacuum drying with induced nucleate boiling for stingless bees honey - N. F., Halim; M. F., Basrawi; N. A., Azman; S. A., Sulaiman; S. B. A., Razak (IOP Publishing, 2022)
Low Temperature Vacuum Drying (LTVD) with induced nucleate boiling is a new method that has been invented to reduce the water content of honey at a lower temperature without damaging the nutrient content of honey. The objective of this study is to investigate the effect of temperature on the dewatering rate by this LTVD method. The honey sample was placed in a pressure vessel and the air from the vessel was removed to create a vacuum condition. This experiment was conducted by using three different temperature which was 40 °C, 45 °C and 50 °C. The honey sample was dewatered for 5 minutes and each condition was repeated three times. The water content before and after the experiment was measured by a digital refractometer. Final water content decrease from 26.5 % to 25.1 % from temperature 40 °C to 50 °C. The dewatering rate increase from 0.14 %/min to 0.28 %/min when the temperature increase from 40 °C to 50 °C. The highest dewatering rate was obtained at 50 °C. However, considering the quality conservation of honey, it is suggested to apply a temperature of 45 °C to get a high dewatering rate while considering the quality of honey. It could be concluded that the temperature effect the final water content and dewatering rate of honey.